Prevention of the musculoskeletal system's dysfunction based on the example of Prevention Program of Spinal Pain Syndrome in Nursing Staff - Matylda Sierakowska; Halina Doroszkiewicz; Dorota Kondzior; Krystyna Klimaszewska; Zofia Jemieljańczuk; Cecylia Dolińska (Nofer Institute of Occupational Medicine, 2019)
Background Most of the medical activities, which are work-related, both static and dynamic are performed by nurses in a forced position. Excessive and improper strain of the musculoskeletal system, especially when lifting and moving patients, is the cause of many injuries of the musculoskeletal system. The work presents the implementation and evaluation of the program concerning the prevention of dysfunction on the part of the musculoskeletal system, addressed to professionally active nurses. Material and Methods The questionnaire was addressed to 125 professionally active nurses, working in conservative units (92%) and outpatient care (8%), suffering from musculoskeletal system dysfunctions, qualifying for the preventive program (ultimately 65 respondents joined the program). The research method was a diagnostic survey, using: the World Health Organization Quality of Life-BREF (WHOQOL-BREF) (scale results are in the range of 4−20 pts), 5-point scale to assess the frequency and intensity of pain and body mass index (BMI). Results The average age of the studied group is 46.6 years old (±8.6), work experience 24.3 (±9.8). A total of 57% of respondents reported pain in the musculoskeletal system, the vast majority of which affected the lumbar spine (89.2%). Constantly occurring complaints were characteristic for nurses, whose average age was 49.5 years (p = 0.0001) and with work experience over 27 years (p = 0.0002), with a BMI value (≥ 25) (p = 0.0038). The average quality of life results were significantly dependent on the intensity of pain (p < 0.05). Conclusions The research shows that pain, escalating with age and duration of the professional activity is a significant factor in lowering the quality of nurses' life. The severity and frequency of experienced ailments significantly decreased after participating in kinesitherapeutic activities. Med Pr. 2019;70(2)189-99